Prediction and Reduction of Prejudice, a New Standard for the Profession of Psychologist - Janaqi, Gerti (Mediterranean Journal of Social Sciences, 2012)
The standard of the profession of psychologist is moving towards a clear objective: the role of psychologists should be put inthe function of upgrading the quality of people’s life in individual and social context. To upgrade the quality of life psychologists have togive directions how to reduce prejudices which have been formed during the new urban and sub urban developments. (Dovidio, 1994).This article will explain why the psychologists are investing big efforts in the methodology related with the identification of the causes ofprejudice. However result of the recent studies underline the fact that psychological instruments often do not always reach to predicthuman behavior. On the other hand before accepting that intergroup prejudices is an integral part of human psyche created by thenorms and cultural values, should carefully examine the effectiveness of institutional norms and values nurtured by psychologicalservices. This psychological "anti-virus" will serve to control the intergroup prejudice. Also, the article emphasizes the role ofpsychological techniques in the reduction of intergroup prejudices.